Integrating STEM Approach in K-12 Science Education Teaching Practice: A Systematic Literature Review - KHUT, SOKHA; Shimizu, KINYA (International Journal of Research in STEM Education, 2023)
The integration of science, technology, engineering, and mathematics (STEM) in K-12 education is widely recognized as a critical means to ensure future prosperity, security, and a skilled workforce in these fields. This integrated STEM approach entails teaching these four STEM disciplines in a cohesive manner. However, several barriers have arisen, including the lack of a clear consensus on the key features of implementing integrated STEM education effectively. There remains uncertainty about which science subjects should be integrated with the other three disciplines and at what level within K-12 science education this integration should occur. Therefore, this study aims to establish a well-defined framework for teaching science through an integrated STEM approach (ISTEMA) and identify the types of integrated STEM disciplines employed in various educational settings through a systematic literature review. Secondary data, including scholarly journal articles and book chapters, were collected through searches in databases such as the Educational Resource Information Center (ERIC) and Web of Science. Data analysis was conducted using within-case and cross-case analysis methods. The findings of the study revealed that the framework of teaching science ISTEMA generally consists of six elements: inquiry-based, engineering-based, technology-based, problem-based, teamwork-based, and robotic-based learning. This approach primarily focuses on primary and lower secondary education. Engineering and technology content is predominantly integrated into the science subject. In primary education, science and engineering and science and technology are extensively used, while in lower and upper secondary education, science, engineering, and mathematics, science, technology, and engineering, or STEM are commonly employed.